Lithium battery positive electrode adhesive, preparation method and application
By introducing low Tg and high Tg monomers into the positive electrode adhesive of lithium battery, a multi-layer core-shell structure is formed, and the ratio of polar groups and monomers is regulated, the problems of low bond strength and easy swelling of existing adhesives are solved, and the effects of high toughness, low swelling and environmental protection are achieved, and the safety and energy density of lithium batteries are improved.
Patent Information
- Application Number
- CN202411701199.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-04
AI Technical Summary
Existing lithium battery positive electrode adhesives such as PVDF have low bonding strength, easy swelling, thermal runaway, environmental protection, etc., which are difficult to meet the safety, environmental protection and low cost requirements of lithium batteries.
By introducing low Tg monomers and high Tg monomers into the adhesive, a multi-layer core-shell structure is formed, the proportion of acrylate monomers is controlled, the ratio of polar groups, polar monomers and non-polar monomers is reasonably set, and the solubility selectivity and surface tension of the adhesive are regulated.
It significantly improves the toughness and bonding properties of the adhesive, enhances the tolerance to the electrolyte, reduces the risk of swelling and dissolution, improves the safety and environmental protection of lithium batteries, and reduces the amount of adhesive used, and improves the overall volume energy density and mass energy density.
Smart Images

Figure CN119552606A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adhesives, and in particular, relates to an adhesive for positive electrodes of lithium batteries, a preparation method and an application thereof. Background Art
[0002] Lithium-ion battery is a secondary battery, mainly composed of positive electrode, negative electrode, separator, electrolyte and battery casing. It mainly relies on the movement of lithium ions between the positive and negative electrodes to work. Due to its advantages such as high energy density and excellent cycle life, it is widely used in energy storage power stations, new energy transportation, smart grids and portable electronic devices and other fields.
[0003] In the prior art, when preparing the positive electrode sheet, an adhesive is usually used to bond the main material to the current collector. Commonly used adhesives include polyvinylidene fluoride (PVDF), which has high chemical stability but has the following disadvantages:
[0004] (1) The bonding strength is relatively low, and the structure is prone to collapse and powder loss during battery charging and discharging; (2) It swells and dissolves in organic electrolytes to form gel, which increases the internal resistance of the battery; (3) The reaction heat released by the chemical reaction with lithium is twice that of fluorine-free adhesives, which can easily cause thermal runaway; (4) When used, it requires the organic solvent N-methylpyrrolidone (NMP) as a solvent, and solvent recovery is required, which is costly; (5) As a fluorine-containing material, it is easy to produce a large amount of hydrogen fluoride during the recycling process of lithium batteries, which damages the environment and is subject to environmental protection policies and export restrictions.
[0005] In short, PVDF is not an ideal environmentally friendly and efficient lithium battery adhesive material.
[0006] Therefore, there is an urgent need to develop an environmentally friendly adhesive with strong bonding ability, high toughness strength, excellent electrolyte tolerance and excellent electrical properties to improve the safety, environmental protection and low cost of lithium batteries.
[0007] In addition, the existing method of preparing pole pieces mostly adopts a process of preparing the main material, adhesive, solvent, etc. into a slurry, then coating it on the current collector, and then drying it. This process has cumbersome post-processing and high energy consumption. Therefore, it is necessary to develop a pole piece production method with simple process, energy saving and low carbon.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a positive electrode adhesive for a lithium battery. The adhesive comprises a low Tg monomer buried in an inner core layer, a high Tg monomer made into a shell portion, and the outer shell is kept as a hard monomer, so that the prepared powder does not stick together and is easy to dissolve, thereby improving the stability and convenience of the prepared adhesive. The low Tg characteristics of the adhesive are ensured by controlling the proportion of acrylic soft monomers in the core layer structure, thereby ensuring the softness and high surface density of the prepared pole piece. The solubility selectivity of the adhesive is regulated by reasonably setting the proportion of polar groups, polar monomers and non-polar monomers, so that the adhesive has a suitable surface tension, exhibits excellent bonding and wetting properties to the current collector and the positive electrode main material, has the advantages of high peel strength, electrolyte tolerance, excellent electrical properties, etc., and meets various technical needs in the working environment of the lithium battery.
[0010] To achieve the above object, the basic concept of the technical solution adopted by the present invention is: to provide a lithium battery positive electrode adhesive, characterized in that a multi-layer core-shell structure is formed by self-suspended core-shell polymerization of a low Tg monomer, a high Tg monomer, a cross-linking monomer, a reactive emulsified monomer, and an initiator;
[0011] The low Tg monomer forms a core layer, and the high Tg monomer forms a shell layer;
[0012] The low Tg monomers include acrylic ester monomers, and the mass of the acrylic ester monomers accounts for 20-60% of the total mass of the raw materials.
[0013] Furthermore, the mass of the acrylic acid ester monomer accounts for 30-40% of the total mass of the raw materials;
[0014] Preferably, the acrylic ester monomer is selected from one or more combinations of isooctyl acrylate, hydroxyethyl acrylate, butyl acrylate, and diallyl phthalate.
[0015] Furthermore, the glass transition temperature Tg of the adhesive is -20 to 80°C.
[0016] In the above scheme, acrylate monomers are soft monomers with a low glass transition temperature. By controlling the proportion of acrylate monomers, the Tg of the adhesive is regulated so that the Tg of the adhesive is controlled between -20 and 80°C, which significantly improves the toughness of the adhesive and the softness of the coating, balances the mechanical properties and heat resistance of the adhesive, and can be made into ultra-high surface density, giving the weight of the less-used adhesive to the positive electrode material, thereby improving the overall volume energy density and mass energy density of the lithium battery.
[0017] Furthermore, the raw materials include polar monomers and non-polar monomers, and the mass ratio of the polar monomers to the non-polar monomers is (20-70:80-30), preferably 1:1;
[0018] Preferably, the polar monomers include acrylic acid, acrylonitrile, acrylamide, hydroxyethyl acrylate, and the non-polar monomers include acrylic ester monomers, styrene, methyl methacrylate, and the like.
[0019] In the above scheme, when the prepared adhesive is used to prepare the electrode, since NMP is a strong polar solvent, it has good solubility for polymers composed of polar monomers, but poor solubility for acrylates, styrene, etc. The electrolyte is a non-polar solvent, and its solubility for polar monomers is limited, but it is very good at dissolving acrylates and styrene, etc., so the ratio of polar and non-polar monomers must be considered, and cross-linking technology must be relied on. In addition, the molecular weight of the adhesive prepared by suspension polymerization is as high as 600,000 or more, and it has a high hydrogen bond density, which increases the difficulty of dissolution, so its ratio is very important, and the mass ratio of polar monomers to non-polar monomers is preferably about 1:1 to ensure its selective solubility performance.
[0020] The prepared adhesive can be quickly dissolved in NMP solvent, but is stable in electrolyte and common non-polar solvents; after the adhesive is formed into a film, the electrolyte saturation absorption rate measured by immersing it in an electrolyte at 60°C is 15%, and it will not excessively swell or dissolve due to long-term contact with the electrolyte, thereby improving the life and stability of the battery.
[0021] Furthermore, the raw material contains polar groups, preferably, the polar groups are selected from one or more combinations of carboxyl, cyano, hydroxyl, amine, amide, modified amide, sulfonic acid, and polyether groups;
[0022] Preferably, the mass of acrylic acid in the core layer structure accounts for 1 to 10% of the mass of the core layer raw material, preferably 3 to 6%;
[0023] Preferably, the mass of acrylic acid in the shell structure accounts for 10 to 50% of the mass of the shell raw material, preferably 20 to 30%.
[0024] In the above scheme, suitable adhesion is crucial for the adhesive, and the number of polar groups has a significant impact on the adhesive performance; in order to ensure that the adhesive has suitable adhesion, the proportion of polar groups is controlled to be 5-50%, and the adhesive has good moisture absorption resistance. Furthermore, the carboxyl group interacts with the amine group, amide group, and hydroxyl group to form hydrogen bonds, which produce strong adhesion and cohesion, which is beneficial to improve the adhesive performance and electrolyte tolerance of the adhesive. Therefore, by limiting the proportion of carboxyl groups, the adhesive performance can be effectively improved, and the adhesive and positive electrode slurry can be ensured to have good fluidity.
[0025] Furthermore, the mass of the low Tg monomer, high Tg monomer, cross-linking monomer, and reactive emulsifying monomer accounts for 20-60%, 5-50%, 0-5%, and 4-5% of the total mass of the raw materials, respectively;
[0026] Preferably, the mass of the low Tg monomer, high Tg monomer, and cross-linking monomer accounts for 30-40%, 10-50%, and 0-5% of the total mass of the raw materials, respectively;
[0027] Preferably, the high Tg monomer is selected from one or more combinations of acrylic acid, acrylamide, acrylonitrile, styrene and methyl methacrylate.
[0028] In the above scheme, by reasonably adjusting the mass proportions of low Tg monomers, high Tg monomers, cross-linking monomers, and reactive emulsifying monomers, the adhesive has a low Tg, meets good bonding properties and high toughness, and solves the brittleness problem when a single polyacrylic acid is used as an adhesive. At the same time, polar groups such as carboxyl, cyano, hydroxyl, amine, and sulfonic acid groups are introduced. Through the selection and quality control of polar groups, the surface tension of the adhesive is designed and regulated, so that the adhesive can have sufficient affinity with the collector surface while having a suitable viscosity, and exhibits excellent bonding and wetting properties.
[0029] At the same time, all raw materials are non-fluorine materials, and no harmful gases such as hydrogen fluoride will be produced when lithium batteries are recycled, and will not be restricted by environmental protection policies.
[0030] Preferably, the crosslinking monomer is selected from a combination of one or more of diacetone acrylamide / adipic dihydrazide, isobutoxy acrylamide, epoxy acrylate, methacryloxytrimethoxysilane, diallyl phthalate, and polyether diacrylate;
[0031] Preferably, the cross-linking monomer is a double cross-linking system selected from diacetone acrylamide / adipic dihydrazide and isobutoxy acrylamide, diallyl phthalate and isobutoxy acrylamide;
[0032] Preferably, the molar ratio of diallyl phthalate to isobutoxyacrylamide is (0.5-1):(0.5-1), more preferably 1:1.
[0033] In the above scheme, by adding a suitable cross-linking monomer, self-cross-linking forms a three-dimensional network structure during use. In this way, not only the high toughness and high adhesion of low Tg are met, but also when immersed in the electrolyte, there is only slight swelling without dissolution, thereby improving the electrolyte resistance of the adhesive, preventing the adhesive from dissolving into the electrolyte to cause the battery structure to collapse, clogging the micropores of the diaphragm, etc., resulting in deterioration of electrical performance and inability to be used normally, improving the stability of the adhesive and battery structure, and improving the long-term cycle characteristics of the battery.
[0034] In addition, the room temperature self-crosslinking effect of the double cross-linking system is obvious, which improves the adhesive's tolerance to the electrolyte. After the adhesive is formed into a film, the electrolyte saturation absorption rate measured when immersed in an electrolyte at 60°C is less than 15%. It will not excessively swell or dissolve due to long-term contact with the electrolyte, thereby improving the life of the battery.
[0035] Preferably, the reactive emulsifying monomer is selected from a combination of one or more of sulfonates with double bonds, carboxylates with double bonds, and polyethers with double bonds;
[0036] Preferably, the sulfonates with double bonds include at least allyl polyoxyethylene sulfonates and vinyl polyoxyethylene sulfonates; the carboxylates with double bonds include at least acrylates; and the polyethers with double bonds include at least allyl polyethers and vinyl polyethers.
[0037] In the above scheme, the reactive emulsifying monomer is a self-emulsifying monomer, which avoids the use of small molecule emulsifiers. This is because small molecule emulsifiers are easy to enter the electrolyte when immersed in the electrolyte, resulting in damage to the battery performance, while self-emulsifying monomers are more beneficial to the battery performance than small molecule emulsifiers.
[0038] The prepared adhesive has an ultra-high molecular weight of more than 20W, which ensures high adhesion of the adhesive and can ensure bonding performance even when used in a small amount.
[0039] A method for preparing a positive electrode adhesive for a lithium battery, for preparing a positive electrode adhesive for a lithium battery as described above, the method comprising the following steps:
[0040] S1: low Tg monomer, cross-linking monomer, self-emulsifying monomer, initiator and solvent are mixed and stirred at high speed according to mass percentage to form a core layer polymerization pre-emulsion;
[0041] S2: taking high Tg monomer, cross-linking monomer, self-emulsifying monomer, initiator and solvent according to mass percentage to prepare shell polymer pre-emulsion.
[0042] S3: adding part of the buffer, self-emulsifying monomer and solvent into the reactor, heating to the specified temperature, and stirring at a constant speed;
[0043] S4: adding the core layer pre-emulsion formed in step S1 into the reactor at a constant speed to perform core layer polymerization;
[0044] S5: adding the shell pre-emulsion formed in step S2 into the reactor at a constant speed to polymerize the shell to obtain an adhesive with a double-layer core-shell structure suspended in a solvent;
[0045] S6: Repeat the above steps S1-S5, and after post-processing, prepare an adhesive suspension having a soft / hard repeatedly crossed multi-layer core-shell structure with a hard monomer as the outer shell.
[0046] S7: drying the suspension obtained through the above steps by rotary evaporation to obtain a powder;
[0047] Preferably, the solvent is water.
[0048] In the above scheme, no suspension aid is used, and the adhesive is prepared into a multi-layer core-shell structure through aqueous suspension polymerization. By controlling the proportion of raw materials and the order of addition, an adhesive powder with a soft / hard repeatedly crossed multi-layer core-shell structure with a hard monomer as the outer shell is prepared, so that the glass transition temperature of the core layer structure is lower than the glass transition temperature of the shell layer structure, the core layer structure has better toughness, and the adhesive forms a film evenly during the bonding process. The film is soft and tough, which improves the bonding performance, distribution uniformity and friction resistance of the adhesive, and takes into account both low-temperature and high-temperature performance. In addition, the high cross-linking density of the core layer makes up for the shortcomings of acrylic ester-based polymers in poor tolerance to electrolytes, thereby ensuring the cycle life of the battery.
[0049] Furthermore, the polymerization reaction temperature is (80-85°C) and the reaction time is (3-4h);
[0050] Stirring is performed during the reaction at a speed of 80 to 300 r / min, preferably 100 to 200 r / min;
[0051] Preferably, the post-treatment includes spray drying, the drying temperature is (80-120° C.), and the moisture content of the adhesive powder obtained after drying is ≤1% to ensure the capacity and the softness of the prepared electrode; Figure 1 As shown, it can be seen from the transmission electron microscope image that the adhesive has a multi-layer core-shell popcorn structure with a particle size of ≤80μm. The small particle size accelerates the dissolution rate, is evenly dispersed and not easy to stick together, which is convenient for subsequent application in the preparation of pole pieces in the positive electrode material and improves the uniformity and bonding stability of the main material on the current collector.
[0052] The molecular structure of the prepared adhesive is: ---(CH2-CHCOONa) m --(CH2CHCONH2) n -(CH2CHROH)x--CH2CH(CH2CHO)yH-CH2CONHR2--
[0053] The structural design and the preparation method design ensure that the decomposition temperature of the adhesive exceeds 390°C and has good stability.
[0054] An application of a lithium battery positive electrode adhesive as described above is used to bond a positive electrode material to a current collector to prepare a pole piece, wherein the positive electrode material is mixed into a slurry by NMP solution, a main material, a conductive agent, and an adhesive, and then coated on the current collector, and pressed into a pole piece of a desired thickness after drying, wherein the surface density of the pole piece is 300g / m 2 .
[0055] Furthermore, the concentration of the NMP solution is 8% to 10%, and the mixing ratio of the NMP solution, the main material, the conductive agent, and the adhesive is (25:100:1:2);
[0056] Preferably, the main material is selected from one of lithium iron phosphate (LFP), lithium manganese oxide (LMO), lithium nickel cobalt aluminum oxide (NCA), and lithium nickel cobalt manganese oxide (NCM), and the conductive agent is selected from conductive carbon black (SP).
[0057] In the above scheme, the consistency of the 8% to 10% NMP solution of the adhesive reaches 2000 to 5000 cps, which is basically equivalent to the consistency of PVDF of the same concentration. When in use, the adhesive is directly dissolved into an 8-10% solution with NMP, and then the solution and the main material of the formula are added to the double planetary mixer in turn to make a uniform slurry, which is then coated on the current collector by a coater and rolled into a pole piece of the required thickness. Compacting, baking, injection, and chemical formation are all carried out according to traditional processes.
[0058] It has good wetting and bonding properties for LFP, LMO, NCA, NCM and SP. The slurry has good stability and fluidity, and can be prepared with a thickness of more than 300g / m 2 The surface density product of
[0059] It should be noted that the traditional adhesive PVDF contains groups that can be hydrolyzed by alkali, so the slurry prepared by it gels when it is wet. The mechanism is as follows:
[0060]
[0061] The adhesive of the present invention does not contain any groups that can be broken by alkali during its preparation process, so no irreversible chemical reaction will occur in the slurry to cause gelation. It has strong alkali resistance and NCM non-gelling properties, which greatly improves the production process.
[0062] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0063] 1. The present invention provides a positive electrode adhesive for a lithium battery. Polar groups such as carboxyl, cyano, hydroxyl, amino, and sulfonic acid groups are introduced into the adhesive system by selecting raw material monomers and controlling the ratio of each monomer. The surface tension of the adhesive is controlled by the design of specific polar groups, so that the adhesive has excellent bonding and wetting properties to the current collector, and improves the bonding firmness and reliability. At the same time, the adhesive has good wetting, dispersion and bonding capabilities for lithium iron phosphate, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, conductive carbon black, etc., and has a wide range of applications and high application flexibility.
[0064] 2. The adhesive provided by the present invention controls the mass percentage of acrylic ester monomers in the raw materials to achieve regulation of the Tg of the adhesive, significantly improves the toughness of the adhesive, and can be made into an ultra-high surface density, giving the weight of the less-used current collector to the positive electrode material, thereby increasing the overall volume density of the lithium battery and increasing the capacity of the lithium battery; at the same time, the adhesive is designed into a multi-layer core-shell structure to meet the suspension polymerization process, low Tg design, drying process, and dissolution selectivity, thereby improving the film formation uniformity, coating performance, bonding performance, electrolyte immersion resistance, and friction resistance of the adhesive.
[0065] 3. The raw materials of the adhesive provided by the present invention are all non-fluorine materials, and no harmful gases such as hydrogen fluoride will be generated during the recycling of lithium batteries, and will not be restricted by environmental protection policies.
[0066] 4. The adhesive provided by the present invention adopts a self-emulsifying monomer to replace the traditional small molecule emulsifier, so as to avoid the small molecule emulsifier remaining in the adhesive and migrating into the electrolyte to affect the battery performance; the double cross-linking system is used to improve the tolerance of the adhesive to the electrolyte. After the adhesive is formed into a film, the electrolyte saturation absorption rate measured by immersing the adhesive in an electrolyte at 60°C does not exceed 15%, and the volume change rate is less than 5%. It will not cause excessive swelling or dissolution due to long-term contact with the electrolyte, thereby improving the life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] The accompanying drawings are part of this application and are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0068] Figure 1 This is a transmission electron microscope image of the adhesive powder prepared in Example 1 of the present invention.
[0069] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0070] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is clearly and completely described below in conjunction with some embodiments. It can be understood by those skilled in the art that the following implementation is only used to explain the technical principle of the present invention and is not intended to limit the scope of protection of the present invention. For example, although the present application describes the steps of the method of the present invention in a specific order, these orders are not restrictive. Without departing from the basic principles of the present invention, those skilled in the art can perform the steps in different orders.
[0071] It should be noted that:
[0072] (1) The test method for peeling force is:
[0073] Tape method: 3m test tape (model Scotch 600-Q33), 1 kg pressure pressed on the positive electrode coating surface, left naturally for 30 minutes; FBS-5D single-arm digital display tensile testing machine 180° peeling, take the average value of three samples.
[0074] Sample preparation conditions: lithium iron phosphate and conductive agent: adhesive (solid): water = 99:1:2, coating thickness 100-120 μm, the sample is baked at 120°C for 5 minutes and then placed in a drying dish for 24 hours before testing.
[0075] Example 1
[0076] This embodiment provides a lithium battery positive electrode adhesive and a pole piece prepared from the adhesive, and the raw material composition is as follows in parts by weight:
[0077] Isooctyl acrylate 35, styrene 22, acrylic acid 18, acrylamide 10, diacetone acrylamide (DAAM) 4, adipic dihydrazide (ADH) 2, NRS-1025 4, acrylonitrile 16, ammonium persulfate 1, sodium bicarbonate 2, deionized water 200;
[0078] The core layer composition is: 31 isooctyl acrylate, 20 styrene, 4 DAAM, 5 acrylonitrile, 2 NRS-1025, 5 acrylic acid, 0.4 ammonium persulfate, and 50 water. All the components are mixed together and emulsified on a homogenizer for 2 minutes to obtain a core layer pre-emulsion;
[0079] Shell composition: 4 isooctyl acrylate, 2 styrene, 13 acrylic acid, 10 acrylamide, 11 acrylonitrile, 0.4 ammonium persulfate, 1.5 NRS-1025, 50 water. All the above components are mixed together and emulsified on a homogenizer for 2 minutes to obtain a shell pre-emulsion;
[0080] The bottom water composition in the reactor is: NRS-1025 0.5, sodium bicarbonate 2, ammonium persulfate 0.2, deionized water 100. All components are added into the reactor in sequence.
[0081] After the bottom water in the reactor is prepared, heat it to 82°C in a sealed container and stir at 120r / min;
[0082] Add the core layer pre-emulsion into the reactor at a constant speed, and complete the injection within 40 minutes. React at a constant temperature for 30 minutes to obtain the core layer emulsion;
[0083] The shell pre-emulsion is added into the reactor at a constant speed, and the injection is completed within 40 minutes. The reaction is carried out at a constant temperature, and the temperature is kept and matured for 30 minutes to obtain an adhesive suspension with a double-layer core-shell structure.
[0084] The suspension obtained by the above reaction is flash dried to obtain PAA adhesive powder;
[0085] According to the ratio of LFP:SP:binder powder:NMP=100:1:2:50.7, add them into the double planetary mixer in sequence and stir for 4 to 5 hours to obtain a positive electrode slurry with uniform fluidity.
[0086] The slurry has a solid content of 66%, a consistency of 5200cps, and a fineness of 8-10um.
[0087] The transmission electron microscope image of the prepared adhesive powder is as follows: Figure 1 shown.
[0088] Comparative Example 1
[0089] The adhesive prepared in Example 1 was replaced by a common positive electrode adhesive (PVDF) on the market to obtain a prepared common electrode sheet.
[0090] Comparative Example 2
[0091] The adhesive prepared in Example 1 was mixed with the NMP solution, the main material, and the conductive agent according to the existing slurry coating method, coated, and dried to prepare the electrode.
[0092] Experimental Example 1
[0093] In this experimental example, the performance of the adhesives in Example 1 and Comparative Example 1 was tested respectively. The test results are shown in Table 1.
[0094] Table 1
[0095]
[0096] It can be seen from Table 1 that compared with traditional positive electrode adhesives, the basic physical and chemical indicators of this experiment have reached the industrialization requirements and have certain performance advantages.
[0097] Experimental Example 2
[0098] In this experimental example, performance tests were performed on the pole pieces prepared in Example 1 and Comparative Examples 1 and 2, and the test results are shown in Table 2.
[0099] Table 2
[0100]
[0101] It can be seen from Table 2 that under the same surface density, the positive electrode sheets produced can meet the softness requirements.
[0102] Experimental Example 3
[0103] In this experimental example, the pole pieces prepared in Example 1 and Comparative Examples 1 and 2 were prepared into batteries in the same manner, and the performance of the prepared batteries was tested respectively. The test results are shown below:
[0104] (1) Battery discharge performance test at different rates:
[0105] Table 3
[0106]
[0107] As can be seen from Table 3, the basic capacity and rate of the electrode produced in this experiment reached the same level as that produced by the traditional positive electrode adhesive.
[0108] (2) Battery low temperature discharge performance test:
[0109] Test conditions: low temperature discharge at -20℃, 0.5c / 1c.
[0110] Table 4
[0111]
[0112] As can be seen from Table 4, the low-temperature discharge performance of this experiment has certain advantages over traditional PVDF.
[0113] (3) Battery storage test:
[0114] Table 5
[0115]
[0116] It can be seen from Table 5 that the high temperature performance of the positive electrode sheet battery produced in this experiment is comparable to that produced by the traditional positive electrode adhesive.
[0117] (4) Battery cycle performance test:
[0118] Table 6
[0119]
[0120] It can be seen from Table 6 that the cycle performance of the positive electrode sheet battery made in this experiment is basically the same as that made with the traditional positive electrode adhesive.
[0121] Experimental Example 4
[0122] In this experimental example, on the basis of Example 1, the mass percentage of the acrylic acid ester monomer in the raw material was changed, and other conditions remained unchanged, to obtain Examples 2-5 and Comparative Examples 3-4, and the properties of the prepared adhesives were tested. The test results are shown in Table 7:
[0123] Table 7
[0124]
[0125] Experimental Example 5
[0126] In this experimental example, on the basis of Example 1, the percentage of polar groups in the total mass of raw materials, the mass percentage of carboxyl groups in the core layer structure and the shell layer structure in the core layer raw material and the shell layer raw material were changed, and other conditions remained unchanged to obtain Examples 6-9 and Comparative Examples 5-6, and the properties of the prepared adhesives were tested. The test results are shown in Table 8:
[0127] Table 8
[0128]
[0129]
[0130] From Table 8, we can see that
[0131] The proportion of polar groups and the distribution of carboxyl groups between the core and shell have a significant impact on the performance of the electrode. The higher the content of polar groups and carboxyl groups, the higher the peel strength of the electrode, the better the electrolyte resistance, but the flexibility is inversely proportional.
[0132] Experimental Example 6
[0133] In this experimental example, on the basis of Example 1, the type and amount of the crosslinking agent were changed, and other conditions remained unchanged, to obtain Examples 10-15, and the properties of the prepared adhesives were tested. The test results are shown in Table 9:
[0134] Table 9
[0135]
[0136] As can be seen from Table 9, when the cross-linking monomer is selected from one or more combinations of diacetone acrylamide / adipic dihydrazide, isobutoxy acrylamide, epoxy acrylate, methacryloxy trimethoxy silane, and diallyl phthalate defined in the present invention, the emulsion polymerization can be self-crosslinked at room temperature to form a three-dimensional network structure. In this way, not only the high toughness and high adhesion of low Tg are met, but also, when immersed in the electrolyte, there is only slight swelling without dissolution, thereby improving the electrolyte resistance of the adhesive, preventing the adhesive from dissolving into the electrolyte to cause the battery structure to collapse, blocking the micropores of the diaphragm, etc., resulting in deterioration of the electrical performance and inability to be used normally, improving the stability of the adhesive and the battery structure, and improving the long-term cycle characteristics of the battery.
[0137] Especially when the cross-linking monomer is a double cross-linking system of isobutoxyacrylamide and diallyl phthalate, and the molar ratio of the two is 1:1, the prepared adhesive has higher bonding performance, lower liquid absorption rate, and higher electrolyte resistance, which can effectively ensure the stability of the battery structure, improve the long-term cycle characteristics of the battery, and increase the battery life.
[0138] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with the present invention can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A lithium battery positive electrode adhesive, characterized in that: A multilayer core-shell structure is formed by self-suspended core-shell polymerization of low Tg monomer, high Tg monomer, cross-linking monomer, reactive emulsifying monomer and initiator; The low Tg monomer forms a core layer, and the high Tg monomer forms a shell layer; The low Tg monomers include acrylic ester monomers, and the mass of the acrylic ester monomers accounts for 20-60% of the total mass of the raw materials.
2. A lithium battery positive electrode adhesive according to claim 1, characterized in that: The mass of the acrylic acid ester monomer accounts for 30-40% of the total mass of the raw materials; Preferably, the acrylic ester monomer is selected from one or more combinations of isooctyl acrylate, hydroxyethyl acrylate, butyl acrylate, and diallyl phthalate.
3. A lithium battery positive electrode adhesive according to claim 1 or 2, characterized in that: The glass transition temperature Tg of the adhesive is -20 to 80°C.
4. A lithium battery positive electrode adhesive according to any one of claims 1 to 3, characterized in that: The raw materials include polar monomers and non-polar monomers, and the mass ratio of the polar monomers to the non-polar monomers is (20-70): (80-30), preferably 1:1; Preferably, the polar monomers include acrylic acid, acrylonitrile, acrylamide, and hydroxyethyl acrylate, and the non-polar monomers include acrylic ester monomers and styrene.
5. A lithium battery positive electrode adhesive according to any one of claims 1 to 4, characterized in that: The raw material contains a polar monomer, and the mass of the polar monomer accounts for 5 to 70% of the total mass of the raw material; Preferably, the polar group is selected from a combination of one or more of carboxyl, cyano, hydroxyl, amine, amide, ether, modified amide, and sulfonic acid groups; Preferably, the mass of the carboxyl groups in the core layer structure accounts for 1 to 10% of the mass of the core layer raw material, preferably 3 to 6%; Preferably, the mass of the carboxyl groups in the shell structure accounts for 10 to 70% of the mass of the shell raw material, preferably 30 to 40%.
6. A lithium battery positive electrode adhesive according to any one of claims 1 to 5, characterized in that: The mass of the low Tg monomer, high Tg monomer, cross-linking monomer, and reactive emulsifying monomer accounts for 20-60%, 5-50%, 0-5%, and 4-5% of the total mass of the raw materials, respectively; Preferably, the mass of the low Tg monomer, high Tg point monomer, and cross-linking monomer accounts for 30-40%, 10-50%, and 0-5% of the total mass of the raw materials, respectively; Preferably, the high Tg monomer is selected from one or more combinations of acrylic acid, acrylamide, acrylonitrile, styrene, and methyl methacrylate; Preferably, the crosslinking monomer is selected from a combination of one or more of diacetone acrylamide / adipic dihydrazide, isobutoxy acrylamide, epoxy acrylate, methacryloxytrimethoxysilane, and diallyl phthalate; Preferably, the reactive emulsifying monomer is selected from a combination of one or more of sulfonates with double bonds, carboxylates with double bonds, and polyethers with double bonds.
7. A method for preparing a positive electrode adhesive for a lithium battery, characterized in that: For preparing a lithium battery positive electrode adhesive as claimed in any one of claims 1 to 6, the method comprises the following steps: S1: low Tg monomer, cross-linking monomer, self-emulsifying monomer, initiator and solvent are mixed and stirred at high speed according to mass percentage to form a core layer polymerization pre-emulsion; S2: taking high Tg monomer, cross-linking monomer, self-emulsifying monomer, initiator and solvent according to mass percentage to prepare shell polymer pre-emulsion. S3: adding part of the buffer, self-emulsifying monomer and solvent into the reactor, heating to the specified temperature, and stirring at a constant speed; S4: adding the core layer pre-emulsion formed in step S1 into the reactor at a constant speed to perform core layer polymerization; S5: adding the shell pre-emulsion formed in step S2 into the reactor at a constant speed to polymerize the shell to obtain an adhesive with a double-layer core-shell structure suspended in a solvent; S6: Repeat the above steps S1-S5, and after post-processing, prepare an adhesive suspension having a soft / hard repeatedly crossed multi-layer core-shell structure with a hard monomer as the outer shell. S7: drying the suspension obtained through the above steps by rotary evaporation to obtain a powder; Preferably, the solvent is water.
8. The method for preparing a positive electrode adhesive for a lithium battery according to claim 7, characterized in that: The polymerization reaction temperature is (80-85°C) and the reaction time is (3-4 hours); Stirring is performed during the reaction at a speed of 80 to 300 r / min, preferably 100 to 200 r / min; Preferably, the post-treatment includes spray drying at a drying temperature of (80-120°C).
9. An application of a lithium battery positive electrode adhesive as claimed in any one of claims 1 to 6, characterized in that: It is used to bond the positive electrode material to the current collector to prepare the pole piece. The positive electrode material is mixed into a fine slurry by NMP solution, main material, conductive agent, and adhesive, and then extruded and coated on the current collector to make a pole piece of the required thickness. The surface density of the pole piece is 150-300g / m 2 .
10. The use of a lithium battery positive electrode adhesive according to claim 9, characterized in that: The concentration of the NMP solution is 8% to 10%, and the mixing ratio of the NMP solution, the main material, the conductive agent, and the adhesive is (25:100:1:2); Preferably, the main material is selected from one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and nickel cobalt lithium manganese oxide, and the conductive agent is selected from conductive carbon black.